Digital Workflow for Immediate Implant Placement and Chairside Provisionalization in the Esthetic Zone - Vincent J. J. Donker; Gerry M. Raghoebar; Arjan Vissink; Henny J. A. Meijer (Hindawi Limited, 2022)
Introduction. Immediate implant placement and immediate chairside provisionalization in the esthetic zone require meticulous treatment planning. A digital workflow that combines intraoral scans and a cone beam computed tomography scan can be used to visualize the surgical and restorative aspects of the treatment and to plan a prosthetically driven implant position. A digital workflow in implant dentistry enables the prefabrication of an individualized CAD/CAM temporary restoration, based on the planned implant position. This could be a predictable method to deliver a screw-retained temporary restoration, directly after static computer-assisted immediate implant surgery. Interventions. Three patients with a failing tooth in the maxillary esthetic zone were treated with immediate implant placement and chairside provisionalization using this digital workflow. After 3 months, a final restoration was placed. Clinical, radiographic, and patient-reported outcome measures were collected prior to implant treatment, 6 weeks after placing the temporary restoration and then 1 month and 1 year after placing the final restoration. Outcomes. At the 1-year follow-up, healthy soft tissues were observed, and peri-implant bone levels were stable. Patient satisfaction after the treatment was high. Conclusion. The three reported cases demonstrate the potential for predictable immediate implant placement and chairside provisionalization using a digital workflow.